IMPROVING THE METHODOLOGY FOR THE DEVELOPMENT OF CREATIVE COMPETENCE OF STUDENTS IN PROFESSIONAL-PEDAGOGICAL ACTIVITIES (ON THE EXAMPLE OF LEARNING FOREIGN LANGUAGES IN HIGHER EDUCATIONAL INSTITUTIONS) - Mukhamedova Guli Bakhodirovna (Journals Park Publishing, 2022)
The teacher's possession of the qualities of creativity directs his personal abilities, natural and social energy to a qualitative, effective organization of professional activity. The pedagogue does not remain creative in itself. His ability for creativity is formed over a certain period of time through consistent reading and learning, work on oneself, and he gradually improves and develops. In this article, the improvement of the methodology for the development of creative competence of students in professional-pedagogical activity is mainly considered and opinions are made on the teaching of a foreign language.
Keywords: Students, future educators, creative competence, foreign language